2009
DOI: 10.1007/s00464-009-0586-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined percutaneous–endoscopic stenting of malignant biliary obstruction: results from 106 consecutive procedures and identification of factors associated with adverse outcome

Abstract: Combined biliary stenting is associated with short- and long-term outcomes equal to those reported in recent series of percutaneous transhepatic stenting. Randomised control trials, including cost-effectiveness analyses, are required to further compare these techniques. Outcomes following combined stenting may be further improved by early recognition and treatment of sepsis and scrupulous management of co-morbid disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 26 publications
6
27
0
Order By: Relevance
“…Our findings did not support the increased 30-day mortality with PTBD, and in fact, we found a lower incidence of 30-day mortality in PTBD patients compared with ERCP patients (0 vs. 6.3 %, respectively). These contrasting results are likely a result of improved imaging, procedural and surgical techniques over the past three decades; a 30-day mortality of 15 % with endoscopic stent placement and 30 % following percutaneous stent placement would be considered high by today's standards [1315]. Speer et al [10] also assessed only short-term outcomes between the different methods of biliary drainage and did not assess whether PTBD patients had different rates of metastases or late-mortality compared with ERCP patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings did not support the increased 30-day mortality with PTBD, and in fact, we found a lower incidence of 30-day mortality in PTBD patients compared with ERCP patients (0 vs. 6.3 %, respectively). These contrasting results are likely a result of improved imaging, procedural and surgical techniques over the past three decades; a 30-day mortality of 15 % with endoscopic stent placement and 30 % following percutaneous stent placement would be considered high by today's standards [1315]. Speer et al [10] also assessed only short-term outcomes between the different methods of biliary drainage and did not assess whether PTBD patients had different rates of metastases or late-mortality compared with ERCP patients.…”
Section: Discussionmentioning
confidence: 99%
“…While PTBD has been shown to improve pruritus symptoms, there is no improvement in patient's quality of life and PTBD potentially establishes a pancreaticodermal tract allowing for tumor cell seeding that can lead to recurrences [10–12]. Despite the controversy surrounding percutaneous drainage, PTBD is often performed in the event of ERCP failure [13]. We sought to evaluate whether PTBD in resectable pancreatic cancer patients influences hepatic recurrence rates and overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, the factors that may affect the ability of a malignant biliary obstruction to be crossed have not been discussed in detail in the existing literature (1)(2)(3)(4)(5)(6)(7)(8). In the studies of Neal et al (9) and Dowsett et al (10), the ability of biliary strictures to be traversed was found to be unrelated to stricture type or location. However, in these studies, combined endoscopic and percutaneous approaches were used.…”
Section: Discussionmentioning
confidence: 97%
“…Crossing the obstruction cannot always be achieved easily. Failure to traverse biliary strictures has been found to be unrelated to the stricture type or location in previous studies (9,10). Mueller et al reported that the likelihood of successful stricture recanalization could not be predicted based on the initial cholangiographic appearance (11).…”
mentioning
confidence: 99%
“…In fact, even according to the indications of the latest guidelines issued by the major scientific societies that worked on this topic, the implantation of this kind of stent is recommended, when life expectancy exceeds 6 months. 1,2,9 This was reasonable at the time of the implantation, since the patient could be reasonably benefit from a combined chemotherapy treatment, which, according to the literature, might have offered a further 3-4 month survival.…”
Section: Placement Of Metallic Stent For Final Palliationmentioning
confidence: 99%